2016
DOI: 10.1186/s12885-016-2489-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and prognosis of gastric cancer in young patients

Abstract: BackgroundThe clinicopathological features and prognosis of gastric cancer in young patients are both limited and controversial. Therefore, the aim of this study was to define the clinicopathological features and prognosis of gastric cancer in young patients after curative resection.MethodsFrom May 2008 to December 2014, 198 young patients (age ≤ 40 years) and 1096 middle-aged patients (55 ≤ age ≤ 64 years) were enrolled in this study. The clinicopathological features and prognosis of gastric cancer in these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
86
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 33 publications
12
86
1
Order By: Relevance
“…Studies have demonstrated that among these ncRNAs, ~18% of lncRNAs are associated with human tumors, compared with only 9% of human protein-coding genes [31], suggesting that lncRNAs could act as major contributors to carcinogenesis and cancer progression. The roles of dysregulated lncRNAs in the proliferation, invasion and migration of many kinds of cancers have garnered increased scientific interest in recent years [3234]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that among these ncRNAs, ~18% of lncRNAs are associated with human tumors, compared with only 9% of human protein-coding genes [31], suggesting that lncRNAs could act as major contributors to carcinogenesis and cancer progression. The roles of dysregulated lncRNAs in the proliferation, invasion and migration of many kinds of cancers have garnered increased scientific interest in recent years [3234]. …”
Section: Discussionmentioning
confidence: 99%
“…[18,20,21] We found that high HOTAIR expression was related to poor differentiation in estrogen-dependent cancers and OSCCs, although the correlation was not identified in previous studies. [1821] Our results showed that HOTAIR expression correlated with a larger tumor size, though the statistical significance was only found in cancers of the respiratory system and there was a publication bias, suggesting that large-scale investigations were required. There are several explanations for the discrepancy in predictive role of HOTAIR expression in various types of cancers.…”
Section: Discussionmentioning
confidence: 94%
“…[1821] Elevated HOTAIR expression is reported to be associated with advanced clinical stage and lymph node metastasis in gastric cancer from a meta-analysis involving 10 studies. [18] However, the relationship between HOTAIR expression and clinical stage is not identified when the data on hepatocellular and gastric cancers are pooled in 4 studies. [20] The clinicopathological value of HOTAIR expression is controversial, and most studies have focused primarily on malignancies of the digestive system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric cancer (GC) is the third most frequent cause of cancer‐related deaths worldwide . The incidence of GC increases after the age of 50 years and peaks in the 60s to 70s . Aging is one of the major factors for GC, like other cancers, yet a substantial subgroup of GCs occurs in younger individuals; this cohort is referred to as GC in young adults (GCYA) .…”
Section: Introductionmentioning
confidence: 99%